2009
DOI: 10.1063/1.3245389
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic-discharge-induced degradation of 1.3μm AlGaInAs∕InP buried heterostructure laser diodes

Abstract: High-peak-power pulsed operation of 2.0 μ m (AlGaIn)(AsSb) quantum-well ridge waveguide diode lasers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…13) The lasing, modulation and other characteristics of AlGaInAs/InP BH lasers subjected to these methods have been reported. [7][8][9][10][11][12][13][14] However, quantitative studies of the regrowth interface quality of BH structures have not been reported.…”
mentioning
confidence: 99%
“…13) The lasing, modulation and other characteristics of AlGaInAs/InP BH lasers subjected to these methods have been reported. [7][8][9][10][11][12][13][14] However, quantitative studies of the regrowth interface quality of BH structures have not been reported.…”
mentioning
confidence: 99%